2020
DOI: 10.1002/brb3.1562
|View full text |Cite
|
Sign up to set email alerts
|

Association of aspirin resistance with 4‐hydroxynonenal and its impact on recurrent cerebral infarction in patients with acute cerebral infarction

Abstract: Objectives To investigate the association of aspirin resistance (AR) with the plasma 4‐hydroxynonenal (4‐HNE) level and its impact on recurrent cerebral infarction (CI) in patients with acute cerebral infarction (ACI) who were receiving aspirin therapy. Methods One hundred and fifty‐four ACI patients who previously received aspirin therapy (100 mg/day) were enrolled. Whole urine (for measuring 11dhTXB2 and creatinine) along with blood (for measuring the plasma 4‐HNE level) were collected at least 7 days after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Next, the remaining 113 articles went through full‐text review, and 83 of them were removed due to predefined inclusion and exclusion criteria. Eventually, 30 articles were included and went through meta‐analysis 19–48 . The study selection process was shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Next, the remaining 113 articles went through full‐text review, and 83 of them were removed due to predefined inclusion and exclusion criteria. Eventually, 30 articles were included and went through meta‐analysis 19–48 . The study selection process was shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…4-HNE is an aldehyde substance closely related to oxidative stress and lipid peroxidation, and oxidative stress is one of the main factors causing ischemic injury, suggesting that the increase of serum 4-HNE might be one of the main mechanisms underlying the increased risk of stroke induced by oxidative stress ( Poli and Schaur, 2000 ; Liu et al, 2020 ). Importantly, a previous study found that serum 4-HNE level was significantly higher in patients with aspirin-resistant cerebral infarction than in patients with aspirin-sensitive cerebral infarction, and the recurrence rate of aspirin-resistant cerebral infarction patients was significantly higher than that of aspirin-sensitive patients with cerebral infarction, indirectly suggesting that serum 4-HNE may be associated with the recurrence of cerebral infarction ( Guo et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…4-Hydroxynonenal (4-HNE) is the most representative substance among the aldehyde products of lipid peroxidation, mainly produced by linoleic acid and arachidonic acid, etc., in lipid peroxidation ( Castro et al, 2017 ; Gallo et al, 2020 ). Importantly, Guo et al (2020) found that 4-HNE was closely related to aspirin sensitivity in patients with acute cerebral infarction, with higher levels associated with a greater risk of aspirin resistance in patients. Moreover, aspirin resistance is considered to be a risk factor for the recurrence of cerebral infarction ( Yi et al, 2013 ; Wiśniewski et al, 2020 ), so 4-HNE may also be associated with the recurrence of cerebral infarction, but there is a lack of direct research evidence.…”
Section: Introductionmentioning
confidence: 97%
“…Homocysteine is thought to influence platelet activity by increasing oxidative stress and causing endothelium dysfunction, which results in reduced nitric oxide (NO) synthesis and bioavailability [ 27 ]. The importance of oxidative stress for platelet activity has been indirectly shown, as its final product, 4-hydroxynonenal (4-HNE), is a predictor of aspirin resistance in patients with acute cerebral infarction [ 28 ]. Homocysteine is also a predictor of 11-dehydro-TXB2 levels in patients with arterial hypertension [ 29 ], which had a high prevalence in our group (93%).…”
Section: Discussionmentioning
confidence: 99%